The potato terms of planting on alternaria blight development and tubers yield - Gavriluck, A.; Rozhok, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2023)
Goal. To study potato terms of planting on yield by different by ripening varieties during the growing in terms of Western Forest steppe of Ukraine. Methods. The researches conducted during 2021—2022 in breeding-seeding rotation on the base Ukrainian Research Plant Quarantine Station of Institute of Plant Protection of NAAS. The experiments conducted on 4 potato varieties of different groups of ripening (Tiras-early, Myroslava — mid-ripe, Fotinia-mid-ripe, and Chervona Ruta — mid-late). The spraying against Colorado beetle conducted by insecticide Ampligo 150ZC, FC. The seeds treating according to the generally approved technique for Western Forest steppe of Ukraine. Results. The researches results proposed about potato terms of planting on disease development during the growing period and its’yield. The potato alternaria blight development observation showed that air temperature, variety resistance define the disease development. The hot weather and humidity deficiency observed during the studies years. It favored the disease development. The early-ripe variety Tiras’dlisease development consisted of 46.5—50.2% and the yield consisted of 4.40—4.45 t/ha. The level of alternaria blight in mid-ripe variety Fotini reached 39.1—42.5%, the yield meaning — 4.47—4.51 t/ha. The disease development for late-ripe variety Chervona Ruta was 33.5—34.9%, the tubers economic yield consisted 4.26—4.30 t/ha. Conclusions. The researches results showed that the following planting term for varieties allowed to decrease level of alternaria blight development and allowed to increase the crop yield.